2002
DOI: 10.1175/1520-0442(2002)015<0809:caivit>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Climatology and Interannual Variability in the Intensity of Synoptic-Scale Processes in the North Atlantic from the NCEP–NCAR Reanalysis Data

Abstract: North Atlantic synoptic-scale processes are analyzed by bandpassing 6-hourly NCEP-NCAR reanalysis data for several synoptic ranges corresponding to ultrahigh-frequency variability (0.5-2 days), synopticscale variability (2-6 days), slow synoptic processes (6-12 days), and low-frequency variability (12-30 days). Climatological patterns of the intensity of synoptic processes are not collocated for different ranges of variability, especially in the lower troposphere. Intensities of synoptic processes demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 96 publications
4
67
0
1
Order By: Relevance
“…The standard deviation of this quantity, frequently entitled "storm track", gives a gross representation of the combined intensities and frequencies of low-pressure and high-pressure systems. It is robust against step-like non-climatic shifts in the data, similar to the recent approach of Wang et al (2006b) Aspects of synoptic variability are also found in neighboring frequency bands such as ultrahigh-frequency variability (0.5-2 days) and slow synoptic processes (6-12 days), each associated with climatological patterns usually not collocated with those for the synoptic band (Ayrault et al 1995;Gulev et al 2002).…”
Section: Quantification Of Variability Without Identification Of Indisupporting
confidence: 72%
“…The standard deviation of this quantity, frequently entitled "storm track", gives a gross representation of the combined intensities and frequencies of low-pressure and high-pressure systems. It is robust against step-like non-climatic shifts in the data, similar to the recent approach of Wang et al (2006b) Aspects of synoptic variability are also found in neighboring frequency bands such as ultrahigh-frequency variability (0.5-2 days) and slow synoptic processes (6-12 days), each associated with climatological patterns usually not collocated with those for the synoptic band (Ayrault et al 1995;Gulev et al 2002).…”
Section: Quantification Of Variability Without Identification Of Indisupporting
confidence: 72%
“…The spectrum of variability of this model is the typical one corresponding to a chaotic system. However, synoptic-scale spectrum is very different from chaotic spectrum (Gulev et al, 2002) and therefore the output of the Lorenz model can not be interpreted as synoptic scale variability in our case. To introduce the synoptic variability inside this model, i.e.…”
Section: Modelmentioning
confidence: 75%
“…Some studies indicate no significant trends in cyclone activity and storminess over the Atlantic/European sector (WASA Group 1998, Bijl et al 1999, Gulev et al 2001, Houghton et al 2001). Other studies demonstrate increasing winter storminess in northern Europe since the 1960s (Alexandersson et al 1998, Ulbrich & Christoph 1999, Gulev et al 2002, Paciorek et al 2002, Pryor & Barthelmie 2003, Zhang et al 2004. A northward shift of the winter storm track has been observed during recent decades (Orlanski 1998, Sickmöller et al 2000, McCabe et al 2001.…”
Section: Introductionmentioning
confidence: 89%